Insulin-like growth factor 1 pathway mutations and protein expression in resected non-small cell lung cancer - Reinmuth, Niels; Kloos, Sebastian; Warth, Arne; Risch, Angela; Muley, Thomas; Hoffmann, Hans; Thomas, Michael; Meister, Michael (Human pathology, 2014)
The purpose of this study was to characterize the prevalence of insulin-like growth factor 1 receptor (IGF1R) mutations, single nucleotide polymorphisms (SNP), and protein overexpression in surgically resected non-small cell lung cancers in relation to patient characteristics and prognosis. This retrospective study was conducted on 304 patients with non-small cell lung cancers who underwent curative pulmonary resection (median follow-up for surviving patients, 3.6 years). IGF1R gene alterations (n = 304) and protein expression (n = 181) were evaluated by polymerase chain reaction-based assays and immunohistochemistry, respectively. Membranous and cytoplasmic staining were analyzed separately. In an exploratory analysis, 1 silent mutation in exon 16 and 3 mutations in introns of the IGF1R gene comprising the tyrosine kinase domain were detected. Moreover, evaluating selected IGF1R SNPs, patients with adenocarcinomas and homozygous for the rs8038415 T-allele had a significantly better survival (P = .025) but no different disease-free survival. Regarding expression, membranous but not cytoplasmic IGF1R staining was higher in squamous cell carcinomas versus other histologies (P < .0001) and showed a trend to longer survival (P = .08). No association between SNP variations and protein expression was found. Membranous IGF1R protein expression is higher in squamous cell versus other histologies but does not correlate with prognosis. SNPs and mutations can be detected and may harbor prognostic value. These alterations may be of interest when evaluating the IGF1R as potential therapeutic target and should receive further research.
Gesehen am 18.08.2020